Value-based marketing and its impact on patient experience and satisfaction: A field study in private hospitals in Baghdad - Basheer Saadoon Hasan (Universitas Negeri Malang, 2026)
This study seeks to find the relationship between value-based marketing, patient experience and patient satisfaction in private hospitals in Baghdad. The study has a significance due to the growing interest of health organizations in marketing strategies that are centred on value-based marketing and patient experience to provide quality health care. A descriptive analytical approach was adopted in this study to test the relationships between the study variables; value-based marketing, patient experience and patient satisfaction. A sample of 280 questionnaires was analysed. Various statistical techniques were used to test the study hypotheses including descriptive statistics, Pearson correlation and linear regression.The results showed that patients' perceptions of value-based marketing practices are good, and the patient experience and patient satisfaction with the health care services are also good. The study also confirmed significant positive associations between value-based marketing, patient experience and patient satisfaction. The results also confirmed that value-based marketing plays a significant role in patient experience and patient satisfaction, and patient experience significantly affects patient satisfaction.